Effect of Overhead Contact Line Pre-Sag on the Interaction Performance with a Pantograph in Electrified Railways - Guiming Mei; Yang Song (Energies, 2022)
In the high-speed rail industry, the overhead contact line erected along the railroad is used to supply the electricity to the high-speed train via a pantograph on the carbody’s roof. This work attempts to explore the effect of contact line pre-sag on the contact quality between the pantograph and the contact line. A nonlinear finite element approach is implemented to build the overhead contact line system with accurate description of the pre-sag of the contact line. Through a nonlinear solution, the effect of contact line pre-sag on the contact force is analysed with different train speeds and tension classes. The analysis result indicates the feasibility of tuning the pre-sag to improve the interaction performance at a given speed and tension class. In the low-speed range, the change of pre-sag does not have a significant effect on the interaction performance. However, when the speed increases up to a certain value, the effect of pre-sag on the contact force is nonnegligible. The increase in tension can reduce the sensitivity of the interaction performance to the pre-sag. An optimisation procedure is implemented to obtain the optimal amount of pre-sag for different train speeds and tension classes. The results indicate a necessity to include a certain amount of contact line pre-sag to maintain an excellent interaction performance at high speed.